Longitudinal Development of Reasons for Living and Dying With Suicide Attempters: A 2-Year Follow-Up Study - Gysin-Maillart, Anja C.; Jansen, Rahel; Walther, Sebastian; Jobes, David A.; Brodbeck, Jeannette; Marmet, Simon (Frontiers in Psychiatry, 2022)
Background Clinical interventions for patients after a suicide attempt might include a focus on Reasons for Living (RFL) and/or Reasons for Dying (RFD). The present study examined the longitudinal development of RFL and RFD in patients with and without a suicide-specific intervention - the Attempted Suicide Short Intervention Program (ASSIP). Methods In this secondary analysis of a 2-year follow-up randomized controlled study, participants completed the Suicide Status Form II to assess RFL and RFD, at baseline, as well as at 6-, 12-, 18-, and 24-months follow-up. Growth models and latent class analysis were used to investigate longitudinal developments in RFL and RFD. Regression models were used to test the association between RFL, RFD and suicidal reattempts and ideation. Results Cross-sectionally and longitudinally, RFD, but not RFL, were associated with suicide reattempts and suicidal ideation. The number of RFD decreased significantly across the 24 month period (from 1.90 at t1 to 1.04 at t5 in the control group and from 2.32 at t1 to 0.51 at t5 in the intervention group), and this decrease was stronger (b = −0.02; p = 0.004) in the ASSIP group than in the control group. There was no overall change in RFL. Three latent trajectories of RFD were identified: a decreasing (n = 77), a steady high (n = 17) and a trajectory with first increasing and then decreasing RFD (n = 26). The proportion of patients in the ASSIP intervention was highest in the decreasing trajectory and lowest in the steady high trajectory. Patients in the steady high trajectory were characterized by worse mental health and fewer social obligations (partner, children) at baseline. Conclusion The results confirm the importance of RFD within the suicidal process and show that the number of RFD can be further reduced over the period of 24 months with short interventions such as ASSIP. The relevance of number of RFL in the suicidal process, as protective factor, was not confirmed. In the subgroup of patients whose RFD did not decrease over a long period of time, there is a particularly high risk of suicidal ideation/behavior. Clinical interventions should focus more closely on RFD, their etiology and maintenance.